INTRODUCTION - LICHTERMAN, Boleslav L. (Journal international de bioéthique et d’éthique des sciences, 2023)
This is the second issue of JIB, dedicated to Russian medical ethics and bioethics broadly defined. The first one was published in 2005 (JIB, vol.16, n.3-4). It had nine chapters, including texts of leading Russian bioethicists Boris Yudin (1943-2017) (who also wrote the Foreword) and Pavel Tishchenko. There have been many changes in the field since. Prof. Mikhail Yarovinsky (who wrote a Russian textbook on bioethics for medical students) died in 2007 [1], followed by Prof. Boris Yudin 10 years later [2]. Since 2008, an academic journal Bioetika (Bioethics) is being published twice a year in Volgograd (see https://bioethicsjournal.ru/ ). Numerous PhD dissertations in bioethics were defended. There are ethics committees at Russian Ministry of Health, research institutions, universities and some hospitals. They are involved in approval of clinical trials, human research projects and animal experimentation. In 2000 Russian Orthodox Church adopted its social concept, which covers bioethical problems (see http://orthodoxeurope.org/page/3/14.aspx). In 2021 a Synodic Commission on Bioethics was established. Russian (bio)ethical landscape would require a separate study. However, as William Somerset Maugham noticed, a novelist “need not eat a whole sheep to know what mutton tastes like; it is enough if he eats a chop. Then, by applying his imagination and his creative faculty to the chop he has eaten, he can give you a pretty good idea of an Irish stew” [3].